Risk of Damage Inside Wooden Cultural Heritage Sites Based on Temperature, Humidity, and Airborne Fungi in South Korea - Ik-Gyun Im; Gyu-Seong Han (BioResources)
The temperature, humidity, and indoor airborne fungi were evaluated at 24 wooden cultural heritage sites (WCHs) (5 from field surveys and 19 from previous studies). Surface contaminating fungi was present year-round in the indoor space of WCHs. Wood decay fungi float only in summer and fall when relative humidity is high. The internal conditions of WCHs, such as an average temperature of 20 °C and a relative humidity of 75% or more, persisted for at least 4 weeks and up to 8 weeks of the year. Accordingly, the growth of surface contaminating fungi and wood decay fungi on wood and Hanji (Korea paper) surfaces was evaluated for 12 weeks. There was no growth at relative humidity of 95% or less. The maximum average relative humidity of 24 WCHs nationwide was 90% or less, which makes it impossible for most wood decay fungi to germinate and grow, and the period when it remained above 95% was very short. Therefore, the indoor space of WCHs is unlikely to be damaged by surface contaminating fungi and wood decay fungi in all periods of the year, as the environment suitable for germination and growth is not created for a long period.